Atividade antiplasmodial in vitro de um derivado da N-metil-isatina (CH3ISACN), e sua toxicidade in silico e in vivo - Melo, Cinthia Rodrigues (2020)
Malaria is a parasitic disease that is highly prevalent worldwide. In 2018, it reached about 228 million people and caused 405,000 deaths. This disease is caused by the parasite of the genus Plasmodium, which is transmitted by man through the bite of the infected female mosquito of the genus Anopheles. One of the main factors that hinder or control malaria is the large number of parasites that are resistant to antimalarials, including an artemisinin and used. Therefore, it is necessary to discover new drugs that have greater efficacy and low toxicity for humans. Morita-Baylis-Hillman ads have several features, including anti-parasitic activities. Thus, the target of our study is an adduct, 2- (3-hydroxy-1-methyl-2-oxoindolin-3-yl) acrylonitrile, also called CH3ISACN. Thus, the present study aimed to investigate the potential of the CH3ISACN adduct as an antimalarial through in vitro studies, and to evaluate its toxicological effects in silico and in vivo. For this, the compound CH3ISACN was exposed to the W2 strain of P.falciparum in human erythrocytes, and evaluated if it was able to reduce parasitemia. It was also verified if it was able to cause hemolysis to erythrocytes. In addition, the theoretical pharmacokinetic and toxicological characteristics of the CH3ISACN adduct were investigated through in silico tests with the software AdmetSAR and Molinspiration. In addition, an acute in vivo toxicological study was carried out, following the experimental protocols adopted at the Toxicological Testing Laboratory (LABETOX) and the OECD Guide 423 (2001). Thus, an initial dose of 300 mg / kg of the test substance was administered to Wistar rats and subsequently, with no deaths, a dose of 2000 mg / kg was administered to other rats of the same species. During the experiment, behavioral parameters, water consumption, feed and weight evolution were evaluated. After 14 days, the animals were euthanized by overdose of anesthetic, and their blood collected for evaluation of biochemical and hematological parameters. The results showed that the CH3ISACN adduct showed good antiplasmodial activity, and low cytotoxicity, with good cell viability. In addition to what was shown to have a good theoretical oral bioavailability and did not present toxicity risks in in silico studies. Furthermore, the CH3ISACN adduct did not cause death in any of the animals, thus presenting a high LD50 and being classified according to GSH in category 5, as having low toxicity. There is also no behavioral change, as well as in the other parameters applicable to the highest dose tested, without causing a significant change. Only a reduction in urea concentration, but that did not bring relevant clinical significance. Finally, either CH3ISACN has a good candidate for malaria treatment. Therefore, it is of great value to continue your study, until reaching clinical phase tests, and thus be included in the therapeutic arsenal against malaria.